Co-Creative Drawing Agent with Object Recognition - Davis, Nicholas; Hsiao, Chih-Pin; Singh, Kunwar Yashraj; Magerko, Brian (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2016)
This paper describes an updated version of a co-creative drawing system called the Drawing Apprentice. The system collaborates with users by analyzing their drawn input and responding in a real time dialogical and improvisational interaction. The current system includes an object recognition module that employs deep learning to classify sketched objects. The system architecture and implementation are described along with its evaluation during a public demonstration during which artists, non-artists, and designers provided feedback about the experience interacting with the system.